2001
DOI: 10.1128/jvi.75.24.11999-12004.2001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Persistent TT Virus Infection, as Determined in Patients Treated with Alpha Interferon for Concomitant Hepatitis C Virus Infection

Abstract: TT virus (TTV) is a recently identified widespread DNA virus of humans that produces persistent viremia in the absence of overt clinical manifestations. In an attempt to shed light on the dynamics of chronic infection, we measured the levels of TTV in the plasma of 25 persistently infected patients during the first 3 months of alpha interferon (IFN-␣) treatment for concomitant hepatitis C virus (HCV) infection. The first significant decline of TTV loads was observed at day 3 versus day 1 for HCV. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
73
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 36 publications
3
73
0
Order By: Relevance
“…Infection is characterised by persistent viraemia and the presence of replicating virus in a wide range of anotomical sites, including bone marrow, lymphoid tissue, lung and liver [6][7][8][9]. As an indication of its great replicative capacity in vivo, studies of the kinetics of clearance of viraemia during interferon-AE therapy have suggested that .10 10 TTV virions are produced every day, with 90% of the virus in plasma cleared and replenished over this period [10].…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Infection is characterised by persistent viraemia and the presence of replicating virus in a wide range of anotomical sites, including bone marrow, lymphoid tissue, lung and liver [6][7][8][9]. As an indication of its great replicative capacity in vivo, studies of the kinetics of clearance of viraemia during interferon-AE therapy have suggested that .10 10 TTV virions are produced every day, with 90% of the virus in plasma cleared and replenished over this period [10].…”
Section: Genetic Diversitymentioning
confidence: 99%
“…These isolates differed by less than 2% in the remainder of their nucleotide sequences. An alignment of these isolates with 79 previously reported TT virus genotypes permits the proposal of TT virus genera and species within the family Anelloviridae in analogy to a previous proposal for the papillomaviruses (family Papillomaviridae).TT viruses (TTV) are ubiquitous in nature and have been demonstrated in more than 90% of serum samples from healthy individuals where they persist over time (14,16,27,41). Viral particles have been purified from feces (17, 34) and, in addition, are excreted in saliva, breast milk, and bile juice (9,38,47,49).…”
mentioning
confidence: 99%
“…TT viruses (TTV) are ubiquitous in nature and have been demonstrated in more than 90% of serum samples from healthy individuals where they persist over time (14,16,27,41). Viral particles have been purified from feces (17, 34) and, in addition, are excreted in saliva, breast milk, and bile juice (9,38,47,49).…”
mentioning
confidence: 99%
“…They display over 30% nucleotide diversity (19) and are classified into five distantly related groups (13). TTVs are ubiquitous in nature and have been demonstrated in more than 90% of serum samples from healthy individuals, where they persist over time (5,10,12,16). A tissue culture system that supports efficient replication of TTV is not yet available (4,13), and this has delayed the study of both TTV genome replication and TTV gene expression.…”
mentioning
confidence: 99%